Head dimorphism in the African python, Python natalensis (Squamata: Pythonidae) from Tanzania - Nicodemus D. Matojo (International Journal of Life Sciences, 2018)
Very little is known about intraspecific variation in the Southern African rock python which is also referred to as the Natal rock python or simply the African python, Python natalensis Smith, 1833 (family Pythonidae of the Order Squamata) mainly due to limited reachability of some members of the species such as the underground types and those inhabiting dense rocks. A recent study has revealed head dimorphism in the snake based on two samples from Bwiru rocky area near Lake Victoria shore in northern Mwanza City of Ilemela District, Tanzania. One morph (the “wedge-headed type”) is the holotype, comprising short triangular head with U-shaped mouth. Another morph (the “shovel-headed type”) is a paratype, comprising a long shovel-shaped head of burrowing design.